Synthesis and Evaluation of Small Molecule Drug Conjugates Harnessing Thioester-Linked Maytansinoids - Chen-Fu Lo; Tai-Yu Chiu; Yu-Tzu Liu; Li-Rung Huang; Teng-Kuang Yeh; Kuan-Hsun Huang; Kuan-Liang Liu; Chia-Yu Hsu; Ming-Yu Fang; Yu-Chen Huang; Tsu-An Hsu; Chiung-Tong Chen; et al. (MDPI AG, 2022)
Ligand-targeting drug conjugates are a class of clinically validated biopharmaceutical drugs constructed by conjugating cytotoxic drugs with specific disease antigen targeting ligands through appropriate linkers. The integrated linker-drug motif embedded within such a system can prevent the premature release during systemic circulation, thereby allowing the targeting ligand to engage with the disease antigen and selective accumulation. We have designed and synthesized new thioester-linked maytansinoid conjugates. By performing in vitro cytotoxicity, targeting ligand binding assay, and in vivo pharmacokinetic studies, we investigated the utility of this new linker-drug moiety in the small molecule drug conjugate (SMDC) system. In particular, we conjugated the thioester-linked maytansinoids to the phosphatidylserine-targeting small molecule zinc dipicolylamine and showed that Zn8_DM1 induced tumor regression in the HCC1806 triple-negative breast cancer xenograft model. Moreover, in a spontaneous sorafenib-resistant liver cancer model, Zn8_DM1 exhibited potent antitumor growth efficacy. From quantitative mRNA analysis of Zn8_DM1 treated-tumor tissues, we observed the elevation of gene expressions associated with a "hot inflamed tumor" state. With the identification and validation of a plethora of cancer-associated antigens in the "omics" era, this work provided the insight that antibody- or small molecule-based targeting ligands can be conjugated similarly to generate new ligand-targeting drug conjugates.